Age increases monocyte adhesion on collagen - Khalaji, Samira; Zondler, Lisa; KleinJan, Fenneke; Nolte, Ulla; Mulaw, Medhanie A.; Danzer, Karin M.; Weishaupt, Jochen H.; Gottschalk, Kay-Eberhard (Scientific reports, 2017)
Adhesion of monocytes to micro-injuries on arterial walls is an important early step in the occurrence and development of degenerative atherosclerotic lesions. At these injuries, collagen is exposed to the blood stream. We are interested whether age influences monocyte adhesion to collagen under flow, and hence influences the susceptibility to arteriosclerotic lesions. Therefore, we studied adhesion and rolling of human peripheral blood monocytes from old and young individuals on collagen type I coated surface under shear flow. We find that firm adhesion of monocytes to collagen type I is elevated in old individuals. Pre-stimulation by lipopolysaccharide increases the firm adhesion of monocytes homogeneously in older individuals, but heterogeneously in young individuals. Blocking integrin αx showed that adhesion of monocytes to collagen type I is specific to the main collagen binding integrin αxβ2. Surprisingly, we find no significant age-dependent difference in gene expression of integrin αx or integrin β2. However, if all integrins are activated from the outside, no differences exist between the age groups. Altered integrin activation therefore causes the increased adhesion. Our results show that the basal increase in integrin activation in monocytes from old individuals increases monocyte adhesion to collagen and therefore the risk for arteriosclerotic plaques.
Gesehen am 08.07.2021